Sibyl, Queen of Jerusalem 1186–1190. By Helen J. Nicholson. New York: Routledge, 2022. ISBN 9781138636514. xiii + 203 pp. £130. - Stephen Donnachie (Royal Studies Journal)
Sibyl, Queen of Jerusalem 1186–1190. By Helen J. Nicholson. New York: Routledge, 2022. ISBN 9781138636514. xiii + 203 pp. £130.